DETECTION OF WHITE SPOT SYNDROME VIRUS (WSSV) IN POST LARVAE OF VANAME SHRIMP (Litopenaeus vannamei) IN THREE DIFFERENT HATCHERY - Fitria, Nurul; Rahmi, Rahmi; Ikbal, Muhamad (Jurnal Perikanan Unram, 2025)
Vannamei shrimp (Litopenaeus vannamei) is a primary aquaculture commodity with an export contribution of up to 85%. However, its production faces challenges due to disease outbreaks, particularly White Spot Syndrome Virus (WSSV). This study aimed to detect the presence of WSSV in post-larvae of vannamei shrimp using the Nested-PCR method in three different hatcheries. The methodology included sample preparation, DNA extraction, DNA amplification through Nested-PCR, electrophoresis, and DNA visualization. The results showed that in the first week of testing, all samples tested negative for WSSV, as no DNA bands appeared at 941bp. However, in the second week, one sample (C5) tested positive for WSSV, indicated by the presence of a DNA band at 941bp, while the other samples remained negative. The prevalence of WSSV infection in this study reached 16.67%. The DNA concentration ranged from 94.5 ng/µL to 166.5 ng/µL, with a purity level between 1.72 and 1.86. These findings suggest that the Nested-PCR method is effective in detecting WSSV presence in vannamei shrimp, providing reliable detection rates.